Innovation with IS usage: individual absorptive capacity as a mediator. Issue 8 (2nd September 2014) - Wang, Weiwei; Liu, Luning; Feng, Yuqiang; Wang, Tienan
Abstract : Purpose: – After information systems (IS) implementation, many organizations report that system underutilization causes the failure to meet expected IS investment returns. It is imperative to understand the way to leverage employees' fullest potential in the IS usage. The paper aims to discuss these issues. Design/methodology/approach: – Anchoring on absorptive capacity (ACAP) theory, the authors develop an employee innovation model. Using survey data and structural equation modeling, this research investigates how perceived organizational levers affect innovation with IS usage (INVU) by introducing individual ACAP as a mediator. Findings: – The authors find general support for the research model through a survey of 205 employees using SAP business intelligence systems in China. The empirical data shows that three interrelated components of individual ACAP significantly contribute to INVU. The findings also suggest that, both fairness of reward and job autonomy are key organizational levers for the utility of individual ACAP. Furthermore, their effects on INVU can be fully mediated by individual ACAP. Originality/value: – The authors empirically unpack and validate individual ACAP in IS innovation situation. The findings provide academics and practitioners with an understanding of how management can inspire employees' potential in implemented system innovation.